Exploring how movement synchronization is related to match outcome in elite professional football - Folgado, Hugo (2019)
Purpose: This study aimed to explore whether the outcome of professional football matches is affected by changes in intra-team movement synchronization. Methods: Positional data from 77 players were collected during 4 matches of an English Premier League team, using the ProZone® tracking system. Intra-team movement synchronization was calculated using the relative phase of all possible pairing combinations of outfield teammates (dyads) and quantified by the overall percentage of time spent near-in-phase (−30o to 30o bin). Per each displacement axis, a 2 × 2 mixed-model analysis of variance (ANOVA) was used to compare the overall dyadic movement synchronization according to the team and the match final outcome. A two-way ANOVA was used to compare movement synchronization according to dyads’ on-field position (defensive or offensive) and match final outcome. Results: Despite individual dynamical trends during each match, the analysed team tended to exhibit lower movement synchronization when losing. Also, dyads with an emphasis in defensive roles seem to present a more synchronized behaviour during the match than dyads with more offensive roles. Conclusions: Findings suggest that movement synchronization may serve as a tactical performance indicator candidate, reflecting the dynamical interaction between teammates and opponents during the match.